2016
DOI: 10.1007/s11420-016-9497-5
|View full text |Cite
|
Sign up to set email alerts
|

All-Arthroscopic Modified Rotator Interval Slide for Massive Anterosuperior Cuff Tears Using the Subdeltoid Space: Surgical Technique and Early Results

Abstract: Background: Traditional intra-articular arthroscopic repair techniques for massive anterosuperior rotator cuff tears are technically demanding and necessitate sacrifice of the rotator interval to enable visualization. An interval slide allows mobilization through release of the medial aspect of the rotator interval, while leaving the lateral, bridging fibers intact. Questions/Purposes: The purpose of this study was to report a novel, arthroscopic, open-equivalent technique using the subdeltoid space to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…14 In their study, Corpus et al. 15 reported a similar technique to fix the suture limbs of both tendons to lateral suture anchors. However, this technique involves 6 loaded sutures in one knotless suture anchor, which is not available in some types of knotless suture anchors.…”
Section: Discussionmentioning
confidence: 99%
“…14 In their study, Corpus et al. 15 reported a similar technique to fix the suture limbs of both tendons to lateral suture anchors. However, this technique involves 6 loaded sutures in one knotless suture anchor, which is not available in some types of knotless suture anchors.…”
Section: Discussionmentioning
confidence: 99%
“…The PROMIS Global-10 is similar in design to the 12-Item Short Form Health Survey (SF-12), another general health PRO measure that has been widely used in assessing patients with rotator cuff pathology and their response to treatment. 8,11,24,28,38 The SF-12 is a short-form version of the SF-36 and is similar to the PROMIS Global-10 in that it has both physical and mental component summaries, with high scores indicating better function and with a mean score of 50 for the US population (range, 0-100). 34,35 Ferreira et al 11 found significantly lower SF-12 physical component scores for patients with rotator cuff arthropathy as compared with matched controls and significantly poorer functional results according to the ASES.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Ferreira et al 11 found significantly lower SF-12 physical component scores for patients with rotator cuff arthropathy as compared with matched controls and significantly poorer functional results according to the ASES. Corpus et al 8 used the SF-12 to measure response to treatment among patients with massive rotator cuff tears treated with an all-arthroscopic modified rotator interval slide, finding a significant improvement in both postoperative ASES scores and SF-12 physical component scores. Similar to these 2 studies, our data showed decreased PROMIS Global-10 physical function scores among patients with rotator cuff pathology, whereas the PROMIS Global-10 mental function scores were similar to the US population average.…”
Section: Discussionmentioning
confidence: 99%
“…Various procedures have evolved over the years in an attempt to address these difficult clinical situations. 1 Surgical techniques such as arthroscopic debridement, capsular release, 4 , 5 interval slides, 6 , 7 margin convergence, 8 , 9 , 10 and partial rotator cuff repair are commonly used during surgical intervention, with the goal of increasing rotator cuff excursion and therefore humeral head coverage, which will allow restoration of the transverse plane force couples. However, if the native tissue is too deficient or immobile even after attempts at mobilization, one may consider the supplemental use of graft augmentation 11 or reconstruction options including interposition allograft, 12 superior capsular reconstruction, 13 , 14 tendon transfers, 15 or even reverse shoulder arthroplasty.…”
mentioning
confidence: 99%